Przestrzeń w wypowiedziach dzieci niewidomych w wieku wczesnoszkolnym - Miler-Zdanowska, Kamila (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
People with visual disabilities acquire knowledge about the surrounding space using other strategies than sighted people. The final stage of gathering this information is independent movement in space as well as the ability to describe it.The aim of the article is to present ways of experiencing space by blind people and strategies to build mental maps in their minds and to present knowledge about space by creating a description of it.The article also presents the results of research on the description of space by blind children in early school age.